Editorial - Smart district heating and energy system analyses - Østergaard, Poul Alberg; Lund, Henrik (International Journal of Sustainable Energy Planning and Management, 2017)
This editorial introduces the 13th volume of the International Journal of Sustainable Energy Planning and Management, which addresses thermal storage systems in district heating systems, simulation of scheduling of energy units as well as the structure of pricing systems for district heating in Sweden. Beyond the area of district heating, the volume probes into the effects of energy price reductions on energy demand in Hungary as well as the geographical distribution of electricity demand and production in Germany.